The extent to which artificial intelligence can Forecast economic growth in Sudan (International Journal of Financial, Administrative and Economic Sciences, 2026)
The study dealt with the range of Artificial Intelligence ability forecasting by economic growth in Sudan, the study aimed to demonstrate the respondents' trends about the range of Artificial Intelligence ability forecasting by economic growth in Sudan. Problem of the study acted in the coming question: What is the range of Artificial Intelligence ability by forecasting with economic growth in Sudan? the study followed the descriptive analytical approach to describe and analyze the primary data, and inductive approach within the literature review which care of Artificial Intelligence technology and its relationship with economic growth. The study achieved to the coming results: the study found that using of Artificial Intelligence in human capital building contributed to economic growth forecasting in Sudan. In addition, the study evidenced that using of Artificial Intelligence when drawing road map to the foreign direct investment led to economic growth forecasting in Sudan. The study recommended with the coming: Necessity of interesting with education and technology education in particular, as well as working power development in order to build a human capital who are up to date for Artificial Intelligence technology, that to participate in economic growth in Sudan. Trial of directive for Artificial Intelligence technology for attracting the foreign direct investment to enhance economic growth in Sudan.
Keywords: Artificial Intelligence; Economic Growth; Forecasting